2013
DOI: 10.1002/ijc.28209
|View full text |Cite
|
Sign up to set email alerts
|

Prognostic and predictive value of estrogen receptor 1 expression in completely resected non-small cell lung cancer

Abstract: Adjuvant chemotherapy (ACT) leads to a modest improvement in survival among patients with completely resected non-small cell lung cancer (NSCLC) but molecular predictors are still rare. Publicly available gene microarray, clinical and follow-up data from two different studies on early-stage NSCLC were used to determine the expression of estrogen receptor 1 (ESR1). Expression values were calculated against clinical and survival data in a training set (n 5 138) and a test set (subpopulation from the adjuvant JBR… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
16
0
1

Year Published

2013
2013
2024
2024

Publication Types

Select...
6
1
1

Relationship

1
7

Authors

Journals

citations
Cited by 22 publications
(20 citation statements)
references
References 39 publications
3
16
0
1
Order By: Relevance
“…Therefore, the upregulation of ERα at 26 weeks likely plays a role in lung carcinogenesis. Our data are consistent with a recent report which showed ERα expression in the early stage of NSCLC [29]. Our study further suggests that ERα and CYP1B1 may function together to promote lung carcinogenesis.…”
Section: Discussionsupporting
confidence: 83%
“…Therefore, the upregulation of ERα at 26 weeks likely plays a role in lung carcinogenesis. Our data are consistent with a recent report which showed ERα expression in the early stage of NSCLC [29]. Our study further suggests that ERα and CYP1B1 may function together to promote lung carcinogenesis.…”
Section: Discussionsupporting
confidence: 83%
“…Five of these studies were carried out in Europe and one was conducted in the USA. Four of them took the median levels of ESR1 mRNA expression as cut-off points to differentiate the positive (≥median) and negative (<median) status [12][13][14], the other two studies considered the highest two tertiles as positive and the lowest tertile as negative status [16]. All included ESR1 studies directly reported unadjusted HRs and their 95%CIs, whilst only three of them provided adjusted HRs and their 95% CIs.…”
Section: Study Characteristicsmentioning
confidence: 99%
“…On the other hand, there were some new studies on RNA expression of ERs in NSCLC [35,36] . Brueckl et al [35] reported that ER-α high expression was of significant positive prognostic value and patients with ER-α high tumors did not have any benefit from adjuvant chemotherapy.…”
Section: D5mentioning
confidence: 99%
“…Brueckl et al [35] reported that ER-α high expression was of significant positive prognostic value and patients with ER-α high tumors did not have any benefit from adjuvant chemotherapy. Atmaca et al [36] demonstrated that ER-α mRNA expression was an independent prognostic factor in metastatic NSCLC.…”
Section: D5mentioning
confidence: 99%